What Will English Higher Education Look Like in 2025? - Huisman, Jeroen; de Boer, Harry; Bótas, Paulo (International Higher Education, 2013)
In light of the recent higher education policy changes in the UK, a scenario study was carried out based on the Delphi-method exploring the longer term impact (2025) of the policies on English higher education. The two scenarios are briefly presented below.